(untitled) (مجلة أبحاث قانونية, 2024)
Thise research aims to establish a criminal law in which the individual is only held accountable for sin, and nothing but sin, and this is what prompts us to say that the existence of material responsibility in the Penal Code in this form indicates a clear defect in the penal policy of the Libyan project, which reflects a conscious return to prehistoric times in determining the provisions of responsibility for misdemeanor crimes, which constitutes a violation of the general principles on which the philosophy of punishment in this legislation is base. This may appear clear through the noticeable contraction of the role of criminal sin that characterizes the will of the perpetrator in front of the material result that is the basis of punishment for these crimes, which indicates explicitly the project’s adoption of the ideas of the objective doctrine in the penal policy that it adopts, even if partially. This explains our focus on studying the legal content of the result in these crimes and the material causality related to them. It is also necessary to shed light on the practical applications that constitute the widest scope of them. It is also necessary to shed light on the practical applications that constitute the widest scope of them through the liability arising from medical errors, and the provisions of the law of retaliation and blood money, in an effort to reach the best solutions to this problem so that the punishment does not go out of its path that revolves between the ideas of benefit and justice.